Portion coherence: enhancing the relevance of introductory courses in teacher education - Biberman-Shalev, Liat; Pinku, Guy; Hemi, Alla; Nativ, Yael; Paz, Omri; Enav, Yarden (Frontiers in Education, 2024)
Studies investigating coherence in teacher preparation often attempt to achieve comprehensive coherence across all components of training to optimize the educational process. Nevertheless, the pursuit of intense coherence presents notable challenges. To address these challenges, we propose the concept of portion coherence, exemplified by the Trio model, which guides preservice teachers in integrating theories into their practices. Through a mixed-method study, we compared pre-service teachers' perceptions of the importance and relevance of introductory courses at the semester's outset and conclusion. While both groups reported a reduction in perceived importance, the intervention group noted a significantly smaller decline in perceived relevance compared to the control group. This suggests that models of portion coherence may enhance the perceived relevance of educational courses, while the perceived relevance of introductory education courses may serve as an indicator of cross-course coherence.